Corrosion kinetics of SAC405 solder alloy in nitric acid and sodium chloride solutions - Mutia, Winston Jose G. (2009.)
The recent direction from the Regulations on Hazardous Substances (RoHS) directive on Waste Electrical and Electronic Equipment to convert to lead-free alloys have challenged the semiconductor industry to find alternatives to the Sn-Pb solder currently being used in printed circuit boards and package leads. This research aims to contribute to the characterization of 95.5Sn/4.0 Ag/0.5 Cu (SAC405) lead free alloy by determining its propensity to corrosion. Components present in SAC405 lead free alloy such as Ag and Cu have tendency for ionic migration and the formation of intermetallics during the corrosion may affect its resistance to corrosion. In this research the corrosion current, corrosion rates, possibility of passivity and the corrosion potential of SAC405 alloy is measured in various corrosivity levels of the environment. The corrosion setup is composed of a potentiostat, electrodes, specimen chamber and a computer to plot and record the data. Results of corrosion measurement show that the rate of corrosion of SAC405 alloy is lowest in water with an icorr value of 10-6 Amps/cm2, and Nitric acid has the highest corrosion rate with an icorr value of 10-3 Amps/cm2, while NaCl lies in between the corrosion rate of water and Nitric acid with an icorr value of 10-4 Amps/cm2. SAC405 undergoes passivation in NaCl solution due to oxidation of Cu in SnAgCu matrix forming Cu2O3. Cu2O3 dissolves at higher potential forming intermetallics of Ag3Sn as revealed in SEM/EDX analysis. In field applications, exposure of SAC405 in moisture is less concern but the reverse is not true in acidic and salty environment.
"June 2009."
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Solder and soldering; Corrosion and anti-corrosives -- Research